2014
DOI: 10.4314/ejesm.v7i2.2
|View full text |Cite
|
Sign up to set email alerts
|

Physico-chemical properties of topsoil under indigenous and exotic monoculture plantations in Omo biosphere reserve, Nigeria

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2016
2016

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 15 publications
0
1
0
Order By: Relevance
“…It has also been reported that there was a substantial increase in soil Zn, Mn, and Cu in sub-Saharan tree canopies (Rao et al, 1990). Chima et al, 2004 noted that a lot of interest is being shown in Nigeria towards incorporation of indigenous tree species like Acacia senegal in reforestation programs since it has the ability to survive well and strongly influence the soil. Moreover, Acacia senegalcan play a key role in combating land degradation .The roots are highly effective in enriching the soil by improving its water and nutrient levels, through the fixation of nitrogen and can also be used to re-vegetate degraded and denuded landscapes.…”
Section: Introductionmentioning
confidence: 99%
“…It has also been reported that there was a substantial increase in soil Zn, Mn, and Cu in sub-Saharan tree canopies (Rao et al, 1990). Chima et al, 2004 noted that a lot of interest is being shown in Nigeria towards incorporation of indigenous tree species like Acacia senegal in reforestation programs since it has the ability to survive well and strongly influence the soil. Moreover, Acacia senegalcan play a key role in combating land degradation .The roots are highly effective in enriching the soil by improving its water and nutrient levels, through the fixation of nitrogen and can also be used to re-vegetate degraded and denuded landscapes.…”
Section: Introductionmentioning
confidence: 99%